2006
DOI: 10.1002/ijc.21879
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of docetaxel and S‐1 by modulating the expression of metabolic enzymes of 5‐fluorouracil in human gastric cancer cell lines

Abstract: We have recently demonstrated in a Phase I/II study that combination chemotherapy with docetaxel (TXT) and S-1 is active against metastatic gastric carcinomas. To elucidate the mechanisms underlying the synergistic effects of these drugs, both the growth inhibitory effects and the expression profiles of enzymes involved in fluorouracil (5-FU) metabolism were examined in vitro and in vivo. TXT alone and in combination with 5-FU inhibited the growth of each of the 5 gastric cancer cell lines that we examined , i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 41 publications
1
67
0
Order By: Relevance
“…Wada et al reported that docetaxel and S-1 combination therapy showed synergistic effects by modulating the expression of the metabolic enzymes of 5-fluorouracil, including thymidylate synthase, dihydropyrimidine dehydrogenase and orotate phosphoribosyl transferase in human gastric cell lines (24). In a phase II study of docetaxel and S-1 combination therapy, the median time to tumor progression was 7.3 months (95% CI, 4.3-10.0 months) (15).…”
Section: Discussionmentioning
confidence: 99%
“…Wada et al reported that docetaxel and S-1 combination therapy showed synergistic effects by modulating the expression of the metabolic enzymes of 5-fluorouracil, including thymidylate synthase, dihydropyrimidine dehydrogenase and orotate phosphoribosyl transferase in human gastric cell lines (24). In a phase II study of docetaxel and S-1 combination therapy, the median time to tumor progression was 7.3 months (95% CI, 4.3-10.0 months) (15).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the preclinical synergism between docetaxel and either S-1 or cisplatin [11][12][13][14][15], it was hypothesized that a combination of docetaxel and either S-1 or cisplatin as a secondline treatment might have better efficacy than docetaxel alone, even after the failure of first-line cisplatin plus either S-1 or capecitabine. On the other hand, compared to doc- In contrast, the addition of S-1 to docetaxel showed a better PFS (median, 2.7 months vs. 1.3 months; p=0.034) than docetaxel alone without substantial impairment in the QoL or increasing toxicity except for all grades of nausea.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, based on its different mechanism of action from those of fluoropyrimidine and platinum and the lack of cross-resistance with these agents, docetaxel is used frequently as a secondline regimen after the failure of fluoropyrimidine-and/or platinum-based first-line therapy. Furthermore, docetaxel shows synergistic antitumor activity with fluoropyrimidines, particularly S-1, by modulating the expression of enzymes involved in the 5-FU metabolism, including thymidylate synthase, dihydropyrimidine dehydrogenase, and orotate phosphoribosyltransferase [11,12]. Docetaxel has also shown synergistic activity with cisplatin in gastric cancer, which was attributed partially to the suppression of the cisplatininduced multidrug resistance-associated protein-1 by docetaxel [13], resulting in the accumulation of intracellular platinum-glutathione complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of S-1 and docetaxel exhibited greater growth-inhibitory effects in human tumor xenograft models than treatment with S-1 alone or docetaxel alone [32]. This synergistic antitumor effect was greater for the combination of S-1 and docetaxel than for a combination of 5-FU and docetaxel.…”
Section: Taxane Combinationmentioning
confidence: 91%